2012
DOI: 10.1016/j.biomaterials.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of the induction of cell pluripotency through metabolic remodeling by thyroid hormone triiodothyronine-activated PI3K/AKT signal pathway

Abstract: Generation of induced pluripotent stem cells (iPSCs) from somatic cells by defined factors is a mechanism-unknown, yet extremely time-consuming process. Inefficient reprogramming leads to prolonged periods of in vitro iPSC selection, resulting in subtle genetic and epigenetic abnormalities. To facilitate pluripotent reprogramming, we have identified the thyroid hormone triiodothyronine (T3) as an endogenous factor that can enhance reprogramming of human dermal fibroblasts (HDF) and umbilical cord mesenchymal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 51 publications
2
48
0
1
Order By: Relevance
“…The initiation phase is also characterised by a metabolic switch from oxidative phosphorylation to glycolysis [65] that occurs around 7 d after induction of reprogramming [66] and involves phosphatidylinositol-3-kinase (PI3K)/AKT signalling [53,67] . For example, Chen et al [67] have demonstrated that the PI3K/AKT pathway was activated during reprogramming in parallel with the upregulation of glycolytic gene expression, showing specifically that AKT activated 2 key glycolytic regulators, AS1060 and PFKB2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The initiation phase is also characterised by a metabolic switch from oxidative phosphorylation to glycolysis [65] that occurs around 7 d after induction of reprogramming [66] and involves phosphatidylinositol-3-kinase (PI3K)/AKT signalling [53,67] . For example, Chen et al [67] have demonstrated that the PI3K/AKT pathway was activated during reprogramming in parallel with the upregulation of glycolytic gene expression, showing specifically that AKT activated 2 key glycolytic regulators, AS1060 and PFKB2.…”
mentioning
confidence: 99%
“…For example, Chen et al [67] have demonstrated that the PI3K/AKT pathway was activated during reprogramming in parallel with the upregulation of glycolytic gene expression, showing specifically that AKT activated 2 key glycolytic regulators, AS1060 and PFKB2. Zhu et al [53] have also shown that PS48, an activator of the PI3K/AKT pathway, is able to enhance reprogramming by upregulating glycolytic genes.…”
mentioning
confidence: 99%
“…PI3K/Akt signaling activation was identified in the initiation phase, being involved in the metabolic switch from oxidative phosphorylation to glycolysis by activation of glycolytic regulators AS1060 and PFKB2 (Chen et al, 2012;Hawkins et al, 2014). Zhu et al demonstrated that Akt activation is capable of increasing reprogramming by upregulation of glycolytic genes (Zhu et al, 2010).…”
Section: Cell Signaling Pathway Modulation Promotes Somatic Cell Reprmentioning
confidence: 99%
“…To validate the multipotency of the isolated hUCMSCs, differentiation to adipogenic and osteogenic lineages were performed as described previously [25,32]. After 3 weeks of induction, cells were stained with the oil red O or alizarin red to detect the presence of neutral lipid vacuoles in differentiated adipocytes or calcium deposition in osteocytes, respectively.…”
Section: Adipogenic and Osteogenic Differentiationmentioning
confidence: 99%